Not All Factors Contribute Equally to European-American and Hispanic Students’ SAT Scores - Brenda Hannon (Journal of Intelligence, 2019)
This exploratory study shows that the contributions of cognitive, metacognitive awareness, performance avoidance, test anxiety, and socioeconomic family background factors to SAT scores (i.e., overall SAT, SAT-V, SAT-M) may vary as a function of ethnicity (i.e., European-American, Hispanic). Four hundred and fifty-seven students, 282 European-American and 175 Hispanic, completed multiple measures of cognitive, metacognitive awareness, social/personality (i.e., test anxiety, performance avoidance, academic self-efficacy), and socioeconomic family background factors, which were used in regression analyses predicting overall SAT, SAT-V, and SAT-M scores. The results show that most factors contributed significantly to overall SAT, SAT-M, and SAT-V scores. In addition, the ethnicity X test anxiety interaction was significant for all three SAT measures, a finding that suggests ethnic differences in the contributions of test anxiety to overall SAT, SAT-M, and SAT-V scores. For European-American students, test anxiety had no influence on overall SAT and SAT-M scores, whereas for Hispanic students test anxiety had a negative influence on overall SAT and SAT-M scores. For SAT-V scores, interpreting the ethnicity X test anxiety interaction was more complicated because both the significant main effect of test anxiety and the ethnicity X test anxiety interaction must be interpreted together. Whereas test anxiety negatively influenced European-Americans’ SAT-V scores, this negative influence was less than the influence it had on Hispanic students’ SAT-V scores. Indeed, for Hispanic students with high test anxiety, this negative influence was profound. Taken as a whole, these results suggest that any theory explaining the SAT may need to take into account multiple predictors as well as the possibility that the contributions of these predictors may vary as a function of ethnicity.